DEPENDENSI HUMAS BPD HIPMI JAWA BARAT DALAM PROSES KOMUNIKASI PUBLIK: PROGRAM KERJA MELALUI MEDIA DIGITAL - Rizqi Ghassani (KOMUNIKA BANGSA, 2026)
Digital media has now become a strategic tool that enables organizations to establish faster, more interactive, and wider-reaching communication. This study aims to analyze the level of dependence on digital media by the Public Relations Department of BPD HIPMI West Java in the process of public communication of the organization's work program. This study uses a descriptive method to understand how digital media is utilized as a means of public communication for the organization. The results of the study show that the dependence on digital media in the public communication of BPD HIPMI West Java develops through four main stages, namely attraction, intensity, amplification, and sustained dependence. This study concludes that digital media plays a very significant role in supporting the effectiveness of organizational public communication. Dependence on digital media not only reflects the organization's adaptation to developments in communication technology, but also demonstrates the transformation of the organization's communication strategy in building more open, interactive, and sustainable relationships with the public.